An experimental census method and estimates of population density of a black howler monkey (Alouatta pigra) highland population in the Sierra Yalijux, Guatemala - Renner, Swen C.; Rieser, Regula; Horwich, Robert H. (Neotropical Primates, 2007)
Groups of the Guatemalan black howler monkey (Alouatta pigra) in a fragmented northern Guatemalan cloud forest in the Sierra Yalijux were analyzed for group composition and size using an ornithological census technique. Audio and visual records were combined to estimate each group’s home range size. The 361 observations in 2002 estimated 50 individuals in seven groups. Two home range classes were observed with ≤ 1.87 ha and ≥ 2.87 ha. Compared to other recent studies, the density of A. pigra in the Sierra Yalijux is considerably higher than in other areas (83.3/km2 vs. 15.1/km2 in Quintana Roo and 23.0/km2 in Palenque) but about half the density found in Belize (178/km2). We discuss the relevance of the ornithology assessment method for howler monkeys.